2003
DOI: 10.1002/mrd.10349
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous reverse transcriptase in murine early embryo development

Abstract: We report that a reverse transcriptase (RT) activity is present in early cleavage stage embryos as determined by a Polymerase chain reaction (PCR)-based detection assay. In an attempt to establish whether this activity plays a role in early embryonic development, we have blocked the endogenous RT by two independent approaches: (1) embryos were exposed to nevirapine, a highly specific nonnucleoside inhibitor of RT activity; (2) anti-RT antibody was microinjected into the nucleus of one blastomere of 2-cell embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 56 publications
2
48
0
1
Order By: Relevance
“…Endogenous reverse transcriptase is involved in proliferation and differentiation of tumorigenic and nondifferentiated cells (56) and is essential in murine early embryo development (57). Inhibition of reverse transcriptase causes developmental arrest during preimplantation, which is associated with reprogramming of gene expression (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous reverse transcriptase is involved in proliferation and differentiation of tumorigenic and nondifferentiated cells (56) and is essential in murine early embryo development (57). Inhibition of reverse transcriptase causes developmental arrest during preimplantation, which is associated with reprogramming of gene expression (57).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of reverse transcriptase causes developmental arrest during preimplantation, which is associated with reprogramming of gene expression (57). Moreover, down-regulation of L1 reverse transcriptase expression with small interfering RNA induces a differentiated morphology in transformed cells (58), and pharmacologic inhibition of reverse transcriptase reduces the growth of human tumor xenografts in athymic nude mice (58).…”
Section: Discussionmentioning
confidence: 99%
“…However, reverse transcriptase may be a critical factor in early mouse embryogenesis. Pittoggi et al (2003) have shown that the impairment of reverse transcriptase (using either the drug nevirapine or an antibody) between the late one-cell and the four-cell stage induces a developmental arrest before the blastocyst stage. In contrast, development was not affected when embryos were exposed to nevirapine after the eight-cell stage.…”
Section: Differentiating Cells and Tissuesmentioning
confidence: 99%
“…31 They further demonstrated that reverse transcriptase inhibition caused a substantial reprogramming of gene expression in arrested embryos, involving both developmental and translational genes. 32 This suggests that endogenous retroviruses, or LINE type products, are playing an important role at the earliest stages of mammalian development. Larsson and colleagues have pioneered the study of HERVs in human embryogenesis, showing that ERV-3, one of the three viruses involved in placentation, is also highly expressed in many human foetal tissues, including adrenal cortex, kidney tubules, tongue, heart, liver and central nervous system.…”
Section: The Implications For Human Development and Normal Physiologymentioning
confidence: 99%